Polysémie, contraintes syntaxiques et baisse de l’ambiguïté dans les langues contrôlées - Bogacki, Krzysztof (Studia Romanica Posnaniensia, 2015)
The article considers such peculiarities of the controlled languages as the choice of lexical units and constraints on their syntax. We review various difficulties that arise during the selection of forms we would like to put in the lexicon of a controlled language. We compare the index of multiple meanings  of the words used to form the vocabulary of a controlled language before and after the lexical control and calculate the change in the ambiguity rate of sentences due to the elimination of polysemy. The words allowed in the lexicon of a controlled language usually have a high polysemy index in the standard language. This is evident especially as far as grammatical and non-technical words are con- cerned. In contrast, technical terms are much more often monosemic. Thus the observation of the “one token = one meaning” principle in the lexicon for the controlled language has a great effect on the decline of ambiguity.